1983
DOI: 10.1007/bf00502619
|View full text |Cite
|
Sign up to set email alerts
|

A regional difference in the distribution of postsynaptic alpha-adrenoceptor subtypes in canine veins

Abstract: The responsiveness of helical venous strips isolated from fifteen different sites in the body of dogs to relatively selective alpha 1- and alpha 2-adrenoceptor agonists was studied, as well as to a non-selective alpha-adrenoceptor agonist. Longitudinal strips of the portal and mesenteric veins and the inferior vena cava between the liver and the renal vein (segment C) were also investigated. All veins contracted to noradrenaline or phenylephrine whereas only seven veins responded significantly to clonidine: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 31 publications
3
19
0
Order By: Relevance
“…Attempts have been made using both in vitro and in vivo experiments to characterize their distribution. It has been relatively difficult to demonstrate postjunctional M2-adrenoceptors in isolated arterial smooth muscle preparations although more success has been achieved with venous tissues (De Mey & Vanhoutte, 1980;1981;Shoji et al, 1983;Langer & Hicks, 1984). Using intact dog preparations, postjunctional a,-and x2-adrenoceptors have been identified in the forelimb (Cavero & Lefevre-Borg, 1981) and hindlimb Gardiner & Peters, 1982;Horn et al, 1982) vascular beds as well as the mesenteric and coronary (Holtz et al, 1982) circulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts have been made using both in vitro and in vivo experiments to characterize their distribution. It has been relatively difficult to demonstrate postjunctional M2-adrenoceptors in isolated arterial smooth muscle preparations although more success has been achieved with venous tissues (De Mey & Vanhoutte, 1980;1981;Shoji et al, 1983;Langer & Hicks, 1984). Using intact dog preparations, postjunctional a,-and x2-adrenoceptors have been identified in the forelimb (Cavero & Lefevre-Borg, 1981) and hindlimb Gardiner & Peters, 1982;Horn et al, 1982) vascular beds as well as the mesenteric and coronary (Holtz et al, 1982) circulations.…”
Section: Discussionmentioning
confidence: 99%
“…These workers suggested that in the femoral vascular bed there was a predominance of oX2-adrenoceptors whereas in the renal bed a,-adrenoceptors predominate. In addition, Shoji et al (1983) found that the distribution and proportions ofpostjunctional a,-and x2-adrenoceptors varied greatly in fifteen isolated veins taken from dogs.…”
mentioning
confidence: 98%
“…Such an interaction between postjunctional xl-and x2-adrenoceptors may also partially explain the wide disparity in the relative potencies of al-and x2-adrenoceptor antagonists found between vascular preparations (see Drew, 1985;McGrath et al, 1989 (Glusa & Markwardt, 1983;Furuta, 1988), prazosin is only 11-35 fold more potent than yohimbine (De Mey & Vanhoutte, 1981;Shoji et al, 1983). Similarly in the canine isolated splenic artery and vein the rauwolscine and prazosin potency ratio against noradrenaline (both agents produced competitive antagonism) was 12 and 3, respectively (Hieble & Woodward, 1984).…”
Section: The Influence Of Angiotensin IImentioning
confidence: 99%
“…The postjunctional a2-adrenoceptors have been shown to be involved in the mediation of vasoconstriction (Flavahan & McGrath, 1980; Zwieten, 1980;Kobinger & Pichler, 1982;Elliot & Reid, 1983;van Meel et al, 1983) and venoconstriction (Shoji et al, 1983;Steen et al, 1984) responses following sympathetic nerve stimulation or noradrenaline infusion. Recent studies have shown that postjunctional al-adrenoceptors predominate in human mesenteric arteries while postjunctional a2-adrenoceptors predominate in human mesenteric veins (Tmrnebrandt et al, 1985).…”
Section: Introductionmentioning
confidence: 99%